Trends in Maternal Mortality by Socio-Demographic Characteristics and Cause of Death in 27 States and the District of Columbia - MacDorman, Marian F. (Obstet Gynecol, 2017)
OBJECTIVE: To analyze recent trends in maternal mortality by socio-demographic characteristics and cause of death and to evaluate data quality. METHODS: This observational study compared data from 2008–2009 to 2013– 2014 for 27 states and the District of Columbia that had comparable reporting of maternal mortality throughout the period. Maternal mortality rates were computed per 100,000 live births. Statistical significance of trends and differentials was evaluated using a two-proportion z-test. RESULTS: The study population included 1,687 maternal deaths and 7,369,966 live births. The maternal mortality rate increased by 23% from 20.6 maternal deaths per 100,000 live births in 2008–2009 to 25.4 in 2013–2014. However, most of the increase was among women aged ≥40, and for non-specific causes of death. From 2008–2009 to 2013–2014, maternal mortality rates increased by 90% for women ≥40, but did not increase significantly for women <40. The maternal mortality rate for non-specific causes of death increased by 48%; however, the rate for specific causes of death did not increase significantly between 2008–2009 (13.5) and 2013–2014 (15.0). CONCLUSIONS: Despite the United Nations Millennium Development Goal and a 44% decline in maternal mortality worldwide from 1990–2015, maternal mortality has not improved in the United States, and appears to be increasing. Maternal mortality rates for women ≥40 and for non-specific causes of death were implausibly high and increased rapidly, suggesting possible over-reporting of maternal deaths which may be increasing over time. Efforts to improve reporting for the pregnancy checkbox, and to modify coding procedures to place less reliance on the checkbox are essential to improving vital statistics maternal mortality data, the official data source for maternal mortality statistics used to monitor trends, identify at-risk populations, and evaluate the success of prevention efforts.